The First Type is Some of the Important Types of the Fredholm Integral and Methods for Solving Them - Sayliyeva Gulrukh Rustam kizi (Journal of Higher Education and Academic Advancement, 2024)
This article reflects on some important types of the Fredholm integral of the first type, which is considered one of the important types of integral equations, methods for calculating them. Specifically about the Schlemilha integral equation, the derivation of the formula that gives its solution has been studied, and some methods for solving integral equations of the same type have been cited.